Design of the interactive Cube-It Toys tool - Amaran Sukumaran (2018)
Cube-It, www.just-cube-it.com, is a patent pending, new State-of-the-Art joining device and system developed by PABensen Pte. Ltd. www.pabensen.com . It connects and locks a joint via a tight-fitting mechanism in a variety of locking configurations. Cube-It can be deployed as a construction play toy which contributes to learning and development of a child thereby improving their STEM (Science Technology Engineering Mathematics) skills.